3
$\begingroup$

This question already has an answer here:

Here is the question $f:X \rightarrow Y$ and $g: Y \rightarrow Z$ are functions and $g \circ f$ is surjective, is $g$ surjective?

My proof: If $g \circ f$ is surjective than $\forall z \in Z \; \exists x \in X \; \mid (g \circ f)(x)=z $ Suppose $f$ is surjective, than $\forall y \in Y \; \exists x \in X\; \mid f(x)=y$. By def. of $(g\circ f)(x)=z$ we have $g(f(x))=z$ and since $f(x)=y$ than we have $g(y)=z$ which implies surjectivity therefore $g$ is surjecive.

Is this the correct way to prove that $g$ is surjective? Or can I not assume surjectivity on $f$

$\endgroup$

marked as duplicate by Najib Idrissi, user147263, N. F. Taussig, Harish Chandra Rajpoot, Ali Caglayan Oct 27 '15 at 11:33

This question has been asked before and already has an answer. If those answers do not fully address your question, please ask a new question.

0
$\begingroup$

You should assume $g \circ f$ is surjective, not $f$. Let $z \in Z$. Choose $x \in X$ so that $g(f(x)) = z$. Let $y = f(x)$. Then $g(y) = z$.

$\endgroup$
  • $\begingroup$ You are assuming surjectivity when you let $y=f(x)$ are you not? $\endgroup$ – adam May 1 '14 at 15:52
  • $\begingroup$ No. $x \in X$ has been chosen. Apply $f$ to get $y$. $\endgroup$ – Umberto P. May 1 '14 at 16:12
  • $\begingroup$ So basically just omit the part where I assume $f$ is surjective and I'm good? But than how does this show $g$ is surjective if there could be a element in $X$ that is not necessairly in $Y$ take $-3$ from the reals and $y=\sqrt{x}$ I dont see how you can just omit it. $\endgroup$ – adam May 1 '14 at 16:16

Not the answer you're looking for? Browse other questions tagged or ask your own question.